Experience of the hijra community in accessing formal healthcare in Dhaka city: an exploratory qualitative study - Kabir, Kazi Sudipta (Brac University, 2023)
This project report is submitted in partial fulfillment of the requirements for the degree of Master of Public Health (MPH), 2023.